Congenital Heart Diseases and Periodontal Diseases—Is There a Link? - Rughwani, Roshan R.; Cholan, Priyanka K.; Victor, Dhayanand J. (Frontiers in Cardiovascular Medicine, 2022)
An understanding in the field of periodontal medicine explains the fact that the oral cavity serves as a niche for numerous pathogenic microorganisms. When these microorganisms or their by-products disseminate to the various parts of the body, they are capable of triggering diseases characterized by an altered host immune-inflammatory response in the anatomically distinct organ. This mechanism is reported in the propagation of cardiovascular diseases with respect to periodontal medicine. Abundant amount of literature suggests an association between atherosclerotic cardiovascular disease and periodontal diseases. However, there is very less data available to highlight the association between periodontal disease and non-atherosclerotic cardiovascular disease, such as congenital anomalies of the heart. This review outlines the relationship between periodontal diseases and congenital heart diseases and also helps us understand whether the presence of periodontal disease can worsen the preexisting congenital cardiac disease.